ROLE OF AN IMPORTANCE OF ACTIVITIES IN SCHOOL ENVIRONMENT - Babu, Anil; Maiwal, Jyoti (Innovare Journal of Education, 2014)
This study is an attempt to discuss the impact of learning activities.For active leaning activities the environment should be prepare less with fear and stress, that should be interesting in learning. The school teachers are conducting any activities it should be according to student's interest , capacity and mental ability. Activities should based on theory of learning by doing, the students can learn more than more things. There are many research scholar Have Been Performing in this activities, It does not mean that we always get hundred percent result of activities ,sometimes unsuccess of activities provide opportunities to do new things. Keywords: Active learning Activities In School Environment